INCLUSIVE PRIMARY EDUCATION IN BANGLADESH FOCUSING STUDENTS WITH DISABILITIES (Proceedings of the World Disability & Rehabilitation Conference, 2018)
Inclusion is a globally recognized educational philosophy that ensures opportunities and participation of all students along with students with disabilities  in all aspects of  school life. The United Nations has recently set target (Goal 4) of the SDGs ensuring quality, equitable and inclusive education for all by the year 2030. Over the years Bangladesh has responded to the international declarations to ensure and promote inclusive education. It is developing model inclusive primary schools across the country. However, many children with disabilities in Bangladesh are still facing exclusion. Data of this phenomenological study were collected from forty school teachers from fifteen  primary schools through FGD and questionnaire guided interviews. Ten classroom teaching were observed and the parents, students, the community people and concerned education officers were interviewed. The social constructivist theory and system theory constructed the theoretical framework of the study. The research found challenges of training, study materials and assistive devices, funds, rigid curriculum and weak coordination among community and schools. It recommended holistic approach and good collaboration among community and school to meet the challenges. The findings might regenerate in depth understanding on inclusive education for policy implementers and other researchers from the context of Bangladesh.
Keywords: Bangladesh; primary education; students with disabilities; inclusive education